Sketching a network portrait of the humber region. Issue 6 (18th March 2014) - Penn, Alexandra S.; Jensen, Paul D.; Woodward, Amy; Basson, Lauren; Schiller, Frank; Druckman, Angela; Gilbert, Nigel; Bullock, Seth
<x xml:space="preserve">Abstract</x> Industrial systems can be represented as networks of organizations connected by flows of materials, energy, and money. This network context may produce unexpected consequences in response to policy intervention, so improved understanding is vital; however, industrial network data are commonly unavailable publically. Using a case study in the Humber region, UK, we present a novel methodology of "network coding" of semistructured interviews with key industrial and political stakeholders, in combination with an "industrial taxonomy" of network archetypes developed to construct an approximation of the region's networks when data are incomplete. This article describes our methodology and presents the resulting network. © 2014 Wiley Periodicals, Inc. Complexity 19: 54–72, 2014